SELF-CONFIDENCE IN ANTHONY McCARTEN’S MOVIE SCRIPT BOHEMIAN RHAPSODY - Tuti Herawati; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2021)
This research was aimed at conducting analysis on self-confidence in Anthony McCarten’s movie script, Bohemian Rhapsody. The self-confidence was analysed by using the theory proposed by Lindenfield (1994) who states that self-confidence consists of self-confidence born and inner self-confidence. Self-confidence born allows someone to show confidence in what he will do. This confidence can make someone believe in himself to achieve what he wants. In confidence born, he claims that a person must develop skills such as communication, assertiveness and feeling control. Inner self-confidence is self-confidence that gives to the individual’s feelings and suppositions that the individual is in good condition. There are three main characteristics that are distinctive to people who have a healthy inner self-confidence. The three characteristics are self-love, self-understanding, and positive thinking. This research used descriptive qualitative method because the discussion was descriptively accomplished. The descriptive qualitative method was applied to explain the self-confidence to get success from the quotations in the movie script. The result result shows that self-confidence born and inner self-confidence vividly played important role to make the protagonist’s success come true.